Hai yang quan yi lun : Zhong Ri Dong Hai zheng yi jie jue ji zhi yan jiu - Wang, Xiuying, 1969- (Beijing : Zhongguo min zhu fa zhi chu ban she, 2012)
Summary in vernacular field only.
Includes bibliographical references (p. [278]-286)
Keywords: United Nations Convention on the Law of the Sea -- (1982); Territorial waters -- China; Territorial waters -- Japan; Diaoyutai (Beijing, China) -- International status; Senkaku Islands -- International status; East China Sea -- International status